Experimental validation of a fluidic pitch link model - Treacy, S.M.; Rahn, C.D.; Smith, E.C. (My University, 2017)
In order to reduce vibration, researchers have been exploring alternatives to conventional rigid pitch links. One viable passive vibration reduction device is the fluidic pitch link. By replacing rigid pitch links on rotorcraft with fluidic pitch links, changes can be made to the blade torsional impedance. At high frequencies, the pitch link impedance can be tuned to change the blade pitching response to higher harmonic loads. Although all have not been demonstrated simultaneously, fluidic pitch links have been shown to be able to reduce rotor power and all six hub forces and moments. A positive impact on aeroelastic stability from several fluidic pitch link designs has been shown for hover and forward flight. This paper will focus on validating the model that has been used in previous research via matching experimental and simulation results. A prototype fluidic pitch link has been designed, built, and tested at LORD Corporation. Displacement, load, and pressure were recorded during testing. Frequency and time response results were compared between simulation and experiment to validate the model. Three different fluid circuits were used, and the model was able to accurately predict performanc e for each of them with the exception of inaccuracy at low frequency due, in part, to the frequency dependence of the elastomer. An additional fourth circuit was tested that included a needle valve. The model did not accurately predict results across the entire range of valve positions, but the model was able to accurately match the dynamic stiffness amplitude using empirical parameters from a parameter study.